Scientific Reasoning in Science Education: From Global Measures to Fine-Grained Descriptions of Students' Competencies - Moritz Krell; Andreas Vorholzer; Andreas Nehring (MDPI AG, 2022)
In modern science- and technology-based societies, competencies that allow citizens to reason scientifically play a key role for science- and technology-based careers as well as for democratic co-determination (e [...]